Diseminasi Revitalisasi Model Pembelajaran untuk Mendukung Pembelajaran Matematika Mendalam bagi Guru Matematika SMP di Kabupaten Maros - Syukriani, Andi; Tahmir, Suradi; Bernard, Bernard; Sabri, Sabri (Jurusan Matematika FMIPA UNM, 2025)
In-depth mathematics learning is considered essential because it provides a meaningful, holistic learning experience and allows students to apply knowledge in various life contexts. However, teachers still face challenges in implementing the learning model, so community service activities at the Maros Middle School Mathematics MGMP are directed at revitalizing the learning model so that students gain a more meaningful and in-depth understanding of mathematics. This activity was carried out at SMPN 1 Maros on July 23 2025. The target of this activity was Junior High School Mathematics MGMP (Subject Teachers' Conference) teachers from various schools in Maros. The number of participants was 10 teachers. The activities were carried out in the form of material presentation sessions, questions and answers and discussions, interview simulations, and self-reflection and self-assessment as a form of personal evaluation of participants' knowledge of strengthening learning concepts. The results obtained were that the PkM activities succeeded in increasing the Maros Middle School Mathematics MGMP teachers' understanding of in-depth mathematics learning by emphasizing the importance of the principles of awareness, meaning, joy, as well as the application of learning models such as PBL that are relevant to the classroom context. Through discussions, practical examples, and strengthening the competence of professional teachers, this activity emphasizes the role of teachers as the main driver in realizing mathematics learning that is adaptive, meaningful, and supports 21st century skills.